Epidemiological study of human intestinal parasites in Sarawak, East Malaysia: A review - Tahar, A.S.; Bilung, L. M; Kasing, Apun; Richard, R.L.; Lim, Y.A.L. (Malaysian Society of Parasitology and Tropical Medicine, 2021)
Intestinal parasitic infections are endemic in rural settings and may account for asymptomatic infections to various health complications. These infections are a cause of concern for communities of lower economic status, especially in developing countries. In Sarawak, indigenous populations residing in geographically inaccessible areas are socially and economically disadvantaged. Through close association with nature, these populations are prone to intestinal parasitism. Currently, scattered information has led to a continual state of neglect at each level of parasitic infection control. This urges for a review of their distribution and transmission based on previous reports to understand the pattern of the diseases in the state which can further address the improvement of mass controlling programs. A literature search was conducted to collect previous reports on human intestinal parasites in Sarawak, East Malaysia from PubMed (Medline), SCOPUS, ScienceDirect and Web of Science from January 2019 to March 2021. Extrapolating the current data in Sarawak which is still considered limited, further interdisciplinary strategies are demanded to give insights in the epidemiology and true prevalence of intestinal parasites in Sarawak. This review addresses for redirection of attitude towards intestinal parasitic infections where it should be given with ample attention by rural populations. In tandem to that, improvement of rural livelihood such as standard of living and sanitation in Sarawak should be accredited as part of the efforts to reduce the number of intestinal parasitic infections in the state. As a control measure, mass deworming should be reconsidered especially to the rural populations.